ID, EGO, AND SUPEREGO OF GEORGIA IN GINNY & GEORGIA SERIES - Rafika Nurhidayah; Fadya, Alya Aqilla (LPPM STBA Pontianak, 2024)
This study aims to describe the id, ego, and superego of Georgia represented in Ginny & Georgia series and the motivation of Georgia's behavior in Ginny & Georgia series. In this study, the writer applied a qualitative approach to elaborate the data related to Ginny & Georgia series. The data was collected through the application of document or artifact analysis. The data analysis focused on the series’ scenes and utterances using Freud's theory of psychoanalysis as the theoretical framework. This study shows an imbalance in Georgia's id, ego, and superego, as evidenced by her involvement in three acts of murders. Furthermore, the motivation of Georgia's behavior towards the murder she committed is her life and death instinct.